O papel do E-moderador em comunidades virtuais : um estudo na rede social Orkut - Lisbôa, Eliana Santana (2009)
In today's society, the technologies have a role of prominence in all social segments, allowing the understanding of the new social structure - the network society - and thus a new economy in which information technology and communication tools are considered indispensable in handling the information and construction of knowledge by individuals. Therefore, this communication will begin addressing the second generation of Internet (Web 2.0). Introducing the concept of social network as a virtual space where information can be shared in a democratic and egalitarian, focusing our attention on Orkut. Then, we discuss the concept of virtual communities and finally, present an analytical study on the role of e-moderator in virtual communities of Orkut that focused on themes: "Web 2.0", "Teacher education" and "ICT". The objective of this study was to hear what they think the e-moderators about the roles they play in the community since the literature identifies as the subject that streamline and motivate the group, contributing to their integration and socialization, to the construction of knowledge through an informal and collaborative learning.